The Effect Of Price Perception And Hedonistic Motives On Iphone Purchase Decisions Among Generation Z In The Special Region Of Yogyakarta - Sujoko Sujoko; Fawwaz Fawwaz; Sri Sri (PT. Hafasy Dwi Nawasena, 2025)
This study was motivated by the massive use of iPhones among Generation Z and findings from previous studies that showed various factors influencing purchasing decisions. The purpose of this study was to analyze the influence of price perception and hedonistic motives on iPhone purchasing decisions among Generation Z in the Special Region of Yogyakarta. This study employs a quantitative approach. The sampling technique used is purposive sampling, with a sample size of 97 respondents who are iPhone users from Generation Z. The research instrument consists of a questionnaire that has undergone validity and reliability tests to ensure the reliability of the measurement tool. The measurement scale used was a 4-point Likert scale, which was then analyzed using SPSS (Statistical Product and Service Solution) for Windows version 22.0. Data analysis was conducted through a series of statistical tests, including multiple linear regression analysis, classical assumption tests, and hypothesis testing. The results indicated that price perception has a positive and significant influence on purchasing decisions, hedonistic motives have a positive and significant influence on purchasing decisions, and price perception and hedonistic motives simultaneously have a positive and significant influence on purchasing decisions. This study implies that Generation Z needs to be wise in considering purchasing decisions, including how to manage hedonistic impulses to align with their needs and financial capabilities.